Implementation of Modernisation Meat Shredding Production in MSMEs Karanggintung Village, Banyumas - Ria Manurung; Sutarno; Erminawati (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
The Abon production process is very conventional and takes one and a half (1.5) days for 5 kg of chicken meat with a workforce of 5 people. The most extended production process is during the pounding and shredding of chicken meat, about one full day for five workers. This impacts the Abon production capacity and the group's monthly turnover. The purpose of the service is to design and provide machine tools for the production modernization process and train the use of machines for the production modernization process. The Pengabdi team carried out the service by providing machine tools to automatically mash and shred chicken meat quickly and accurately with a time that was previously 1.5 days to 15-20 minutes for 5 kg to improve the quality and quantity of shredded production at Partners. Then, I will assist in sustainable industrial management and training on the use and maintenance of engineering machines in a participatory manner. the production process is not optimal, which has an impact on sales turnover, has been resolved by the Service Team by providing 1 unit of shredded meat shredding machine during the implementation of this service activity. The lack of innovation in the product, because it is still one type of original flavour, Chicken Meat Shredded, has also been resolved by the Service Team by diversifying the product through testing the shredded meat shredded rendang flavour machine.